2015
DOI: 10.1007/s11071-015-2410-9
|View full text |Cite
|
Sign up to set email alerts
|

The comparison and complex analysis on dual-channel supply chain under different channel power structures and uncertain demand

Abstract: In this paper, a dual-channel supply chain composed of one manufacturer and one retailer is discussed. The manufacturer sells its products to its customers, becoming the rival of the retailers. In this case, we consider two scenarios in which the manufacturer holds either asymmetric or symmetric channel power as the retailer. According to the changing demand, we develop the dynamic game models for the two scenarios and analyze the models' dynamic behavior. The corporations' profits and system stability are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 18 publications
2
58
1
Order By: Relevance
“…Some scholars studied the influence of channel structure on participants. For example, Ma and Xie [2] considered one manufacturer and one retailer in a dual-channel supply chain, the manufacturer holds either asymmetric or symmetric channel power compared to the retailer. The result found that the system stability should be easier to maintain with asymmetric channel power.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars studied the influence of channel structure on participants. For example, Ma and Xie [2] considered one manufacturer and one retailer in a dual-channel supply chain, the manufacturer holds either asymmetric or symmetric channel power compared to the retailer. The result found that the system stability should be easier to maintain with asymmetric channel power.…”
Section: Introductionmentioning
confidence: 99%
“…Ma and Si [14] established a continuous Bertrand duopoly game model with twostage delay to investigate the influence of delay and weight on the complex dynamic characteristics of the system. Ma and Xie [15] analyzed the comparison and complexity on a dual-channel supply chain under the different channel power structures and uncertain demand. Ma and Xie [16] discussed the impact of loss sensitivity on a mobile phone supply chain system stability based on the chaos theory.…”
Section: Introductionmentioning
confidence: 99%
“…These findings show that the indicated parameters should be kept in a certain range; otherwise the systems will enter chaos through flip bifurcations. Ma and Xie [12] discussed a dual-channel supply chain and found that when firms hold asymmetric channel power, as the game leader, the manufacturer could get more profit than when they hold symmetric channel power. Hong et al [13] proposed a framework of promoting food information traceability for estimating costs and developing appropriate price strategies.…”
Section: Complexitymentioning
confidence: 99%